Savaging the civilized : Verrier Elwin, his tribals, and India - Guha, Ramachandra (Oxford University Press, 1999)
"Verrier Elwin (1902-1964) was unquestionably the most colorful and influential non-official Englishman to live and work in twentieth-century India. A prolific writer, Elwin's ethnographic studies and popular works on India's tribal customs, art, myth and folklore continue to generate controversy.".